Modelling the association between biomarkers and clinical outcome: An introduction to nonlinear joint models. Issue 4 (3rd February 2022) - Kerioui, Marion; Bertrand, Julie; Bruno, René; Mercier, François; Guedj, Jérémie; Desmée, Solène
Abstract : Nonlinear joint models are a powerful tool to precisely analyse the association between a nonlinear biomarker and a time‐to‐event process, such as death. Here, we review the main methodological techniques required to build these models and to make inferences and predictions. We describe the main clinical applications and discuss the future developments of such models.